Impact of turmoil on the health care delivery system in Kashmir” Kashmir, heaven on earth? - Rathor, Mohammad Yousuf; Kausar, R. (Faculty of Medicine, International Islamic University Malaysia, 2006)
KASHMIR – once known as Jannat-e-Benazir (the heaven unmatched) - is a unique Himalayan Valley having a soothing climate, lofty mountains with snow covered peaks, high-altitude meadows, gushing streams and gurgling springs with crystal clear water. Throughout the history, it has been recognized as one of the most beautiful places in this part of the world. Its scenic exquisiteness is augmented by the beauty of its inhabitants, who are most hospitable and their mutual harmony have been legendary. However, this unmatched beauty is challenged presently by the untold miseries of the inhabitants of this place, who suffer in this war torn place.